2017
DOI: 10.1103/physreva.95.013631
|View full text |Cite
|
Sign up to set email alerts
|

Quantum crystallography of Rydberg-dressed Bose gases on a square lattice

Abstract: We numerically investigate the quantum crystallographic phases of a Rydberg-dressed Bose gas loaded on a square lattice by using the mean-field Gross-Pitaevskii model. For a relatively weak lattice confinement, the phases of ground state undergo amorphism, polycrystal, and polymorphism following the increase of the blockade radius, and if the confinement is stronger, a single crystal with a specific filling factor will be formed. In order to distinctively characterize these phases, the structure function is al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Recently, it was demonstrated that a structural phase transition of optical patterns from a hexagonal lattice to two types of square lattices may occur in an EIT-based Rydberg gas with a microwave dressing between two Rydberg states [16]. These investigations enriched our understanding on the MI and related pattern formation in systems with repulsive (or with both repulsive and attractive) Kerr nonlinearities, which are topics explored in different physical systems by many research groups, from which new pattern formation mechanisms for conservative nonlocal nonlinear systems were found in recent years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, it was demonstrated that a structural phase transition of optical patterns from a hexagonal lattice to two types of square lattices may occur in an EIT-based Rydberg gas with a microwave dressing between two Rydberg states [16]. These investigations enriched our understanding on the MI and related pattern formation in systems with repulsive (or with both repulsive and attractive) Kerr nonlinearities, which are topics explored in different physical systems by many research groups, from which new pattern formation mechanisms for conservative nonlocal nonlinear systems were found in recent years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 80%
“…From this we formulate a useful form of the bound involving a single unit cell without the need to consider various angles. Also, our general techniques allow us to explore conditions under which 2D crystalline states exhibit anisotropic superfluidity (see [29]), hence revealing situations where the tensorial nature of the superfluid fraction manifests.…”
Section: Introductionmentioning
confidence: 99%
“…In the appendix we outline an alternative but equivalent method for calculating the superfluid fraction tensor via the effective mass of the BEC in a crystalline state [29,30]. We show that the effective mass can be determined by a solving a linearized problem, which is equivalent to solving for the Hartree excitations of the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that MI may occur in such systems even the Kerr nonlinearity is repulsive, or has both repulsive and attractive parts [36][37][38][39][40][41][42][43][44], which provides the possibility to realize spontaneous symmetry breaking [45] and generate spatially extended, ordered structures in nonlocal nonlinear media. Various self-organized patterns were found [42][43][44][46][47][48], especially the ones of atomic density formed in Rydberg-dressed [40,[49][50][51][52][53][54] and dipolar [55][56][57][58][59][60] Bose-Einstein condensates.…”
Section: Introductionmentioning
confidence: 99%